Comparison of Polyfilament Suture (Vicryl Rapide-0) & Monofilament Suture (Monocryl 3-0) in the Repair of Mediolateral Episiotomies: Vicryl Rapide-0 and Monofilament Suture in the Repair of Mediolateral Episiotomies - Zaidi, Mahrukh; Sohail, Irum; Sadiq, Hasina; Riaz, Marium; Fatima, Shafaq (Pakistan Journal of Health Sciences, 2025)
Episiotomy remains a common obstetric procedure, and the choice of suture material can influence postoperative pain, wound healing, and maternal satisfaction. Objectives: To compare Monocryl and Vicryl Rapide for mediolateral episiotomy repair in terms of pain, wound healing, complications, and patient satisfaction. Methods: A quasi-experimental study was conducted at the Gynecology Department, KRL General Hospital, Islamabad, from August 2022 to October 2023. Sixty women (18–45 years) undergoing spontaneous vaginal delivery were randomized into two groups (n = 30 each). Skin closure was done with Monocryl 3-0 (study group) or Vicryl Rapide 3-0 (control group), while deeper layers were closed with Vicryl Rapide 0 in both groups. Pain was assessed using the Visual Analog Scale (VAS). Results: Baseline demographics were comparable between groups (p>0.05). The study group reported significantly lower pain at 1 hour (p=0.001), 3 hours (1.53 ± 1.41 vs. 3.30 ± 2.38, p=0.001), 6 hours (0.97 ± 1.59 vs. 2.63 ± 2.01, p=0.001), after defecation (0.63 ± 0.93 vs. 2.00 ± 1.46, p<0.001), after urination (0.53 ± 0.82 vs. 1.63 ± 1.35, p<0.001), and on day 7 (p<0.001). Wound healing was significantly better with Monocryl (p=0.005), and patient satisfaction was higher (p=0.001). No infections occurred in the Monocryl group, compared to 6.7% in the control. Conclusions: Monocryl demonstrated clear superiority over Vicryl Rapide for episiotomy repair, offering reduced pain, improved wound healing, and higher maternal satisfaction.